The Pessary Process: Spanish-Speaking Latinas’ Experience - Sevilla, Claudia (2012)
INTRODUCTION: Little is known about women’s experience with conservative management of pelvic organ prolapse. We sought to understand the experiences of Spanish-speaking women who choose a pessary. METHODS: Spanish-speaking women from a urogynecologic pessary clinic were recruited for this study. Interviews were conducted and the women were asked about their pessary experience including questions involving symptom relief, pessary management, and quality of life. All interview transcripts were analyzed using the qualitative methods of Grounded Theory. RESULTS: Sixteen Spanish-speaking women who had been using a pessary for at least one month were enrolled in this study. Grounded theory methodology yielded several preliminary themes, in which one major concept emerged as a pessary adjustment process. In this process patients had to first decide to use a pessary, either because of physician’s recommendations or out of personal choice. Second, the patients entered an adjustment period in which they learned to adapt to the pessary, both physically and mentally. Lastly, if the patients properly adjusted to wearing a pessary they experienced relief of bothersome symptoms. CONCLUSIONS: Our findings demonstrate that Spanish-speaking women go through a process in order to adjust to a pessary. Furthermore, the physician has a major role in not only determining a woman’s decision to use a pessary, but also whether she can adjust to wearing the pessary. This process is most successful when patients receive comprehensive management from a healthcare team of physicians and nurses who can provide individualized and continuous pessary care.